PJMHS 2021
DOI: 10.53350/pjmhs2115103530
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of hepatitis C virus infection in Type 2 Diabetic patients

Abstract: Background: Infection caused by hepatitis C virus is common and important issue of public health in Pakistan. The risk factors associated with type 2 diabetes mellitus and hepatitis C virus has common association. Objectives: To find out the frequency of hepatitis C virus in Type 2 Diabetes mellitus patients and to assess the association between Type 2 Diabetes mellitus and hepatitis C virus. Methodology: This was descriptive study piloted at the Department of Medicine Hayatabad Medical Complex Peshawar for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Our finding is in concurrence with the results reported by Solomon and Mehta (28,29). The prevalence of HCV infection has been described in different continents in Table 3 (11,(30)(31)(32)(33)(34)(35)(36)(37). In contrast, some studies have reported low prevalence of HCV infection in patients with type 2 diabetic (38)(39)(40)(41).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding is in concurrence with the results reported by Solomon and Mehta (28,29). The prevalence of HCV infection has been described in different continents in Table 3 (11,(30)(31)(32)(33)(34)(35)(36)(37). In contrast, some studies have reported low prevalence of HCV infection in patients with type 2 diabetic (38)(39)(40)(41).…”
Section: Discussionsupporting
confidence: 92%
“…However, the rate of HCV prevalence varies from 0.5% to 10% in different regions of the world (11). In Iran, the seroprevalence of HCV among blood donors is about 0.13% and in general population is less than 1% (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of a second investigation were likewise similar [17]. HCV was also shown to be frequent among diabetics in a research by Ali et al [18]. The findings of the Knobler and Schattner study [19] also showed a strong link between HCV infection and Type 2 Diabetes mellitus.…”
Section: Discussionsupporting
confidence: 61%
“…It was previously shown that the higher risk of HCV infection in type 2 diabetic patients may be related to frequent parenteral exposure (self-monitoring of blood glucose, insulin injection, blood transfusion) (22,23). Moreover, blood transfusion, mother-to-child transmission, non-sterile medical procedures and traditional practices (scarification, tattoo, and circumcision) were considered as common routes of HCV infection in Sub-Saharan Africa, despite the absence of confirmatory studies (16,24).…”
Section: Discussionmentioning
confidence: 99%